Electroencephalography From Basic Research to Clinical Applications - Nakano, Hideki (IntechOpen, 2021)
The development of non-invasive brain function measurement has enabled the knowledge that brain activity is the basis of human behavior and mental activity. Electroencephalography (EEG) is a method that measures the electrical nerve activity (primary signal) in the brain. EEG characteristics include high time resolution and low spatial resolution, but recently it has become possible to estimate the source of EEG signals due to advances in analysis and measurement techniques. Moreover, in the medical field, EEG is usually used as examination equipment, but it has been used as a rehabilitation tool to control human behavior and mental activity in recent years. This book outlines basic research and clinical applications of EEG.